The Influence Of Financial Variables On The Performance Of Pdam In Central Sulawesi Province - Dwi Apriliani; Syallom Marcellino Tamauka; Moh. Rifki; Meta Aulia; Erwinsyah (Universitas Muhammadiyah Palu, 2026)
This study aims to empirically analyze the effect of Return on Equity (ROE), Operating Ratio, Cash Ratio, Collection Efficiency, and Solvency on the performance of Regional Drinking Water Companies (PDAM) in Central Sulawesi Province. The study emerges from a research gap in previous literature, where some studies emphasize the importance of profitability and liquidity, while others indicate that operational factors and collection efficiency contribute more dominantly to the performance of regional water utilities. The research data were obtained from PDAM financial reports recorded at BPPSPAM for the period 2018–2023 and analyzed using multiple linear regression with SPSS version 25. The analysis results indicate that, simultaneously, all financial variables have a significant effect on PDAM performance, with a coefficient of determination (R²) of 0.686. Partially, Operating Ratio and Collection Efficiency exert a positive and significant influence, whereas ROE, Cash Ratio, and Solvency do not show a significant effect. These findings confirm that cost efficiency and effective billing processes are key determinants in enhancing PDAM performance. Practically, the results provide implications for PDAM management to focus strategies on controlling operational costs, improving billing system quality, and strengthening financial governance to support the sustainability of clean water service provision.